Amyloid-Associated Neuron Loss and Gliogenesis in the Neocortex of Amyloid Precursor Protein Transgenic Mice - Bondolfi, Luca (J Neurosci, 2002)
APP23 transgenic mice express mutant human amyloid precursor protein and develop amyloid plaques predominantly in neocortex and hippocampus progressively with age, similar to Alzheimer's disease. We have previously reported neuron loss in the hippocampal CA1 region of 14- to 18-month-old APP23 mice. In contrast, no neuron loss was found in neocortex. In the present study we have reinvestigated neocortical neuron numbers in adult and aged APP23 mice. Surprisingly, results revealed that 8-month-old APP23 mice have 13 and 14% more neocortical neurons compared with 8-month-old wild-type and 27-month-old APP23 mice, respectively. In 27-month-old APP23 mice we found an inverse correlation between amyloid load and neuron number. These results suggest that APP23 mice have more neurons until they develop amyloid plaques but then lose neurons in the process of cerebral amyloidogenesis. Supporting this notion, we found more neurons with a necrotic–apoptotic phenotype in the neocortex of 24-month-old APP23 mice compared with age-matched wild-type mice. Stimulated by recent reports that demonstrated neurogenesis after targeted neuron death in the mouse neocortex, we have also examined neurogenesis in APP23 mice. Strikingly, we found a fourfold to sixfold increase in newly produced cells in 24-month-old APP23 mice compared with both age-matched wild-type mice and young APP23 transgenic mice. However, subsequent cellular phenotyping revealed that none of the newly generated cells in neocortex had a neuronal phenotype. The majority were microglial and to a lesser extent astroglial cells. We conclude that cerebral amyloidosis in APP23 mice causes a modest neuron loss in neocortex and induces marked gliogenesis.